2013
DOI: 10.1093/eurheartj/eht258
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in patients with stable coronary heart disease: an international perspective

Abstract: AimsDespite the known benefits of regular exercise, the reasons why many coronary heart disease (CHD) patients engage in little physical activity are not well understood. This study identifies factors associated with low activity levels in individuals with chronic CHD participating in the STABILITY study, a global clinical outcomes trial evaluating the lipoprotein phospholipaseA2 inhibitor darapladib.Methods and resultsPrior to randomization, 15 486 (97.8%) participants from 39 countries completed a lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 22 publications
(31 reference statements)
7
53
1
Order By: Relevance
“…A higher level of leisure-time activity and walking have been shown to be associated with graded lower incidence of atrial fibrillation, with progressively lower risk occurring as leisure-time activity and both the distance walked and pace of walking increased [17]. It has also been reported that physical activity in patients with stable coronary heart diseases was most often limited by non-specific symptoms such as shortness of breath, fatigue, and weakness [18]. It is possible that symptoms such as weakness and reduced vitality in part are associated with lower levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of leisure-time activity and walking have been shown to be associated with graded lower incidence of atrial fibrillation, with progressively lower risk occurring as leisure-time activity and both the distance walked and pace of walking increased [17]. It has also been reported that physical activity in patients with stable coronary heart diseases was most often limited by non-specific symptoms such as shortness of breath, fatigue, and weakness [18]. It is possible that symptoms such as weakness and reduced vitality in part are associated with lower levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were assessed from the questions “How is your current mood?” (denoted as “depressed mood”) and “Have you lost interest in activities or hobbies that normally give you pleasure?” (denoted as “loss of interest”), with possible responses of never or rarely, sometimes, often , or always . Physical activity was assessed from the total hours of moderate‐intensity (4 metabolic equivalents) and vigorous‐intensity (8 metabolic equivalents) physical activity during an average week . A healthy diet was classified using a Mediterranean diet score based on responses to a simple food‐frequency questionnaire .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the well-known benefits of physical activity and exercise training, most of eligible cardiovascular patients do not benefit from cardiac rehabilitation programs[52], and these patients are more likely to taking less exercise[53]. Exercise levels may even decrease after the diagnosis of heart disease.…”
Section: Physical Activity In Secondary Prevention Of Cardiovascular mentioning
confidence: 99%
“…Exercise levels may even decrease after the diagnosis of heart disease. The least active subjects are more likely to be older, male, obese and present symptoms during common activities such as short distance walking[53]. …”
Section: Physical Activity In Secondary Prevention Of Cardiovascular mentioning
confidence: 99%